Development of Interactive Powerpoint-Based English Learning Media for Grade XI Students MAN 1 East Lampung - Safitri, Lia; Suhono, Suhono; Pratiwi, Wiwied; Hidayah, Yayuk; Sari, Yeasy Agustina (CV. Creative Tugu Pena, 2024)
This article aims to develop interactive powerpoint-based English learning media for grade XI students of MAN 1 East Lampung. This research method is research and development (R&D) with the ADDIE model. ADDIE research stages include analyze, design, development, implementation, and evaluation. This research instrument is an interview sheet, validation sheet, student and teacher response questionnaire. This research data analysis technique uses qualitative and quantitative descriptive techniques. Qualitative descriptive analysis was conducted on the results of interviews. Quantitative descriptive analysis was carried out on the results of expert validation and student and teacher response questionnaires. Based on the analysis conducted, the percentage of feasibility results from material experts was 92.5% with the criteria